Reticulated Platelets: Changing Focus from Basics to Outcomes - Hannawi, Bashar; Hannawi, Yousef; Kleiman, Neal S. (Thrombosis and Haemostasis, 2018)
Platelets play an essential role in the pathophysiology of atherothrombosis. Reticulated platelets (RPs) are the youngest platelet population in the circulation; their presence is an indicator of platelet turnover. Circulating levels of RPs are increased in patients with coronary artery disease and stroke. Preliminary indications are that the proportion of circulating RP is associated with the likelihood of ischaemic events such as acute coronary syndrome and stroke. Plausible mechanisms include: (1) increased participation of these platelets in thrombosis due to messenger ribonucleic acid that may be translated to active proteins, (2) lack of exposure to anti-platelet drugs since they are newly released from the bone marrow or (3) their presence is a non-specific marker of inflammation. In this state-of-the-art review, we discuss the implication of RP in coronary artery disease and in hypo-responsiveness to the most commonly used anti-platelet drugs.
Keywords: coronary artery disease; stroke; reticulated platelets; immature platelets; platelet function test; anti-platelet drugs